Report on the situation in Catalonia from the point of view of the Union General de Trabajadores - Unión General de Trabajadores de España
1936-08 Everybody in Catalonia, especially in responsable quarters, is becoming increasingly afraid of the Anarchist danger. It is the first time that Anarchists have arms at their disposal on such a large scale. They are already making the worst misuse of them. While firearms are so scarce at the fronts that Republican workers and soldiers who leave the other side to join the militia must be Kept inactive pending the arrival of more rifles, thousands of young anarchists are driving all day about Barcelona wasting petrol and displaying themselves in the lounges of comandeered hotels, or walking up and down the Ramblas with their girls and their rifles or army pistols. It is a question of "vigilance", they say, but apparently it is rather a question of keeping Barcelona under their terror. In fact, they are for the present moment the actual rulers of Catalonia. The government is purely decorative. Banditry grows more widespread every day. Altho it is extremely difficult to get the facts, there is no doubt about it that an average of twenty people a day are arbitrarily arrested by F.A.I. men, brought to the local "investigation committee" of the F.A.I., and sumarily executed as fascists or, [while others]if they are lucky, released with apologies. The government is absolutely helpless, and even responsable Anarchist leaders such as Garcia Oliver, who is multiplying appeals in the F.A.I. organ, "Workers'Solidarity" against "individual actions which stain the revolution", have obviously lost control over a large section of the rank and file. Conditions are apparently much better on the front, altho discipline is something quite new to the Anarchists, as being contrary to their doctrine. It is almost certain that most of the executions are simply due to personal vengeance. The case was mentioned to me of a businessman who was shot merely because he only employed affiliated members of the U.G.T. and not of the Anarcho-Syndicalist C.N.T. Comarera said to me that I should let you know that they urgently need arms for the test of power which he considers as unavoidable between the constructive Socialist, Communist and Trade-Union forces and the F.A.I. If the IFTU found it impossible to supply them with arms, they would like to get at least the money for purchasing them. Apparently there is a strong hope of a split in the F.A.I, since Garcia Oliver and others seem to realize that a new policy would become necessary for them, that the problem of raw materials, of payment of wages and so forth was impossible to solve with Anarchist theories. I must add that the communists, who have their own experience with the Anarchists in Russia, are no less determined than the Socialists to crush them. There is also another problem, which seems to me very nasty, that of the Trotskist P.O.U.M., which responsable T.U. quarters describe however as comparatively negligible. But I have the impression that they are very active and successful in touting for supporters among the dregs of the population round the port, and among international adventurers. Communists at the front told me that they were behaving the worst in the villages which they occupied, and even anarchists speak scornfully of their low morals. 292/946/10/145